Modelagem computacional de redes genéticas regulatórias - Gupta, Shantanu (2016)
In biology, regulatory networks are sets of macromolecules, mostly proteins and RNAs that interact to execute task. The main players in regulatory networks are DNAbinding proteins, also called transcription factors as they modulate the first step in gene expression. A gene regulatory network (GRN) is a set of genes or proteins that interact with each other to control a specific cell function. Gene regulatory networks are important in development, differentiation and to respond to environmental cues. Gene regulatory networks (GRNs) are the on-off switches of a cell operating at the gene and/or protein level. The modeling methods can be broadly categorized into continuous and discrete. In this work , we dedicate attention to discrete models on cell senescence models for Astrocyte [35], the modelling of drug synergies to control gastric cancer [38], and we also wrote a paper about Discrete and Continuous Model, advantage or disadvantage of these models and a list of available softwares for using these kind of approaches.